Constructing Heterogeneous Interface by Growth of Carbon Nanotubes on the Surface of MoB2 for Boosting Hydrogen Evolution Reaction in a Wide pH Range - Sun, Jianhang; Guo, Feifan; Ai, Xuan; Tian, Yuyang; Yang, Jin; Zou, Xiaoxin; Zhu, Guangshan (Small (Weinheim an der Bergstrasse, Germany), 2024)
Transition metal diborides represented by MoB2 have attracted widespread attention for their excellent acidic hydrogen evolution reaction (HER). Nevertheless, their electrocatalytic performance is generally unsatisfactory in high‐pH electrolytes. Heterogeneous interface engineering is one of the most promising methods for optimizing the composition and structure of electrocatalysts, thereby greatly affecting their electrochemical performance. Herein, a heterostructure, composed of MoB2 and carbon nanotubes (CNTs), is rationally constructed by boronizing precursors including (NH4)4[NiH6Mo6O24]·5H2O (NiMo6) and Co complexes on the carbon cloth (Co,Ni–MoB2@CNT/CC). In this method, NiMo6 is boronized to form MoB2 by a modified molten‐salt‐assisted borothermal reduction. Meanwhile, Co catalyzes extra carbon sources to grow CNTs on the surface of MoB2. Thanks to the successful production of the heterostructure, Co,Ni–MoB2@CNT/CC exhibits remarkable HER performance with a low overpotential of 98.6, 113.0, and 73.9 mV at 10 mA cm−2 in acidic, neutral, and alkaline electrolytes, respectively. Notably, even at 500 mA cm−2, the electrochemical activity of Co,Ni–MoB2@CNT/CC exceeds that of Pt/C/CC in an alkaline solution and maintains over 50 h. Theoretical calculations reveal that the construction of the heterostructure is beneficial to both water dissociation and reactive intermediate adsorption, resulting in superior alkaline HER performance. A carbon nanotubes‐modified MoB2 on a carbon cloth integrated electrode is prepared by an operable heterogeneous interface engineering strategy. The reasonably constructed heterogeneous interface provides abundant active sites and optimizes intermediate adsorption barriers, thus improving its electrocatalytic HER performance in a wide pH range. Especially at high current density, its activity is comparable to Pt.